Orbital Lateral Cantal Distance Can Predict the Cephalometric Characteristic of Mandible in Iranian Population. Issue 8 (November 2021) - Solhjoo, Somayeh; Sayadi, Mahtab; Navid, Shadan; Toolee, Heidar
Abstract : Abstract: Orbitofacial anthropometrics have become an important tool used in reconstructive surgery. The authors attempt to evaluate the relation between orbital lateral canthal distance and the cephalometric characteristic of mandible in Iranian population. In a cross-sectional study, anthropometric parameters of face in 200 subjects (100 males and 100 females) with mean age of 34.39 ± 18.83 were evaluated by three-dimensional computed tomography imaging. In this study, there was not a significant difference in the age of sex groups ( P = 0.183). Also, there was no significant difference in the left and right mandible angle in different sex groups ( P = 0.25, P = 0.124, respectively). There were significant differences in the anterior mandible distance, inferior mandible angle distance ( P = 0.0001) and lateral cantus distance of sex groups ( P = 0.0001). There was a significant correlation between lateral contuse distance and left mandible angle ( r = 0.226, P = 0.001), right mandible angle ( r = 0.283, P = 0.00), mandible angle ( r = -0.266, P = 0.00), anterior mandible angle distance ( r = 0.655, P = 0.00), and inferior mandible angle distance ( r = 0.582, P = 0.00). Here, we conclude that orbital lateral canthal distance can predict the cephalometric characteristic of mandible in Iranian population. Abstract : Supplemental Digital Content is available in the text